The Ijārah bi al-’Amal Analysis of Wage-Setting Contract Teachers in Aceh Jaya - Amrizal Hamsa; M. Ikhwan; Ismul Karimah (Seutia Hukamaa Cendekia, 2023)
This study investigates the payment of wages as compensation for labor services under Islamic law, specifically the concept of ijārah bi al-’amal or renting services for completing a particular job. The research aims to answer two main questions: first, how is the wage setting system for contract teachers established in Teunom District, and second, how does the ijārah bi al-’amal contract perspective influence the wage system? Using a qualitative research method, data was collected through observation, interviews, and documentation and then analyzed descriptively to achieve the research objectives. The study reveals that the contract teacher wage-setting system in Aceh Jaya is based on the Aceh Jaya Regional Regulation No. 63 of 2015 concerning Regional Assistance Contract Workers, which considers the educational background of the workers in determining their wages. In terms of the ijārah bi al-’amal contract, the study finds that the wages given to contract teachers in Teunom District do not follow the standards outlined in the wage regulations. Although the wages are considered under the agreement/contract, they only fulfill the primary needs (dharuriyat) and do not meet the proper needs referred to in the regulations.